Aplicação de Tecnologia de Detecção Proximal no Crescimento de Videiras: Uso da Fluorescência da Clorofila a Como Indicador da Eficiência Fotossintética Em Vitis Labrusca L - Monte, Francisco Diogo Medeiros do (2024)
This work aimed to identify chlorophyll a fluorescence parameters using a proximal sensor, the Handy-PEA, as indicators of photosynthetic efficiency of Vitis labrusca L. BRS Carmem and Niagara Rosada cultivars. Two pruning periods (September and April) were chosen to evaluate the performance of the cultivars, in a 2x2x2 factorial, with two cultivars on two properties in two pruning times. The chlorophyll index and chlorophyll a fluorescence were evaluated weekly in each cultivar, following the phenological phases of the crop. The maximum chlorophyll index was obtained in phenophases (F) F4 and F5 in both cultivars and properties in the first pruning. Using the Mixed Data Factor Analysis test, 12 chlorophyll a fluorescence parameters were chosen with the potential to describe the effects of the pruning season on the two cultivars. Among these parameters, the one that represents the performance of the final electron acceptors of photosystem I (RE0/RC) stood out, as evidenced by the evolution of photosynthetic efficiency throughout the phenological phases in both cultivars and in the two pruning periods.